Pengaruh Pemberian Aromaterapi Lemon Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester I - Putriyaza, Lala; Mariza, Ana; Putri, Ratna Dewi; Yuviska, Ike Ate (MIDWIFERY JOURNAL, 2023)
Background: Nausea (nausea) and vomiting (emesis gravidarum) are normal in pregnant women but if nausea and vomiting occur >10 times a day, it can disrupt the balance of nutrition, electrolytes, and can affect the general condition so that if vomiting increases to hyperemesis it can cause fetal growth disturbed. The incidence of emesis gravidarum in pregnant women is 50-90%, while hyperemesis gravidarum reaches 10-15% in Lampung Province from 19,896 pregnant women. Nausea in pregnancy can be overcome by using complementary therapies, including aromatherapy. The purpose: of the study was to determine the effect of giving lemon aromatherapy on emesis gravidarum in pregnant women TM 1 at the Wonogiri Health Center.Methods: This type of research is quantitative and pre-experimental research design with one group pre-post test design. The population of this study were all 34 pregnant women. . The sample in this study amounted to 34 pregnant women. The sampling technique uses saturated sampling, that is, all members of the population are sampled.  The object of this research is emesis gravidarum and lemon aromatherapy. The research was carried out at the Wonogiri Health Center, Kotabumi, North Lampung in June - July 2021. Data collection used a questionnaire sheet. Data analysis was univariate and bivariate (t test).The results: of the study on average nausea and vomiting before being given lemon aromatherapy was 8.7, while the average nausea and vomiting after being given lemon aromatherapy was 6.4. Conclusion: There is an effect of giving lemon aromatherapy on emesis gravidarum in pregnant women TM 1 at the Wonogiri Health Center with a p-value of 0.000. Suggestion: It is hoped that hoped can do lemon aromatherapy as an effort to reduce nausea and vomiting during pregnancy Keywords: Lemon Aromatherapy, Nausea Vomiting ABSTRAK Latar Belakang: Mual (nausea) dan muntah (emesis gravidarum) suatu yang normal pada ibu hamil namun jika mual muntah terjadi >10 kali dalam sehari, dapat mengganggu keseimbangan gizi, cairan elektrolit, dan dapat memengaruhi keadaan umum sehingga jika muntah bertambah menjadi hiperemesis dapat mengakibatkan pertumbuhan janin terganggu. Angka kejadian emesis gravidarum pada wanita hamil yaitu 50-90%, sedangkan hiperemesis gravidarum mencapai 10-15% di Provinsi Lampung dari jumlah ibu hamil yang ada yaitu sebanyak 19.896 orang, Rasa mual dalam kehamilan dapat ditanggulangi dengan menggunakan terapi pelengkap antara lain dengan aromaterapi.Tujuan penelitian: diketahui pengaruh pemberian aromaterapi lemon terhadap emesis gravidarum pada ibu hamil TM 1 di Puskesmas Wonogiri.Metode: Jenis penelitian kuantitatif dan desain penelitian pre eksperimen dengan rancangan one group  pre post test design. Populasi penelitian ini adalah seluruh ibu hamil sebanyak 34 orang. . Sampel pada penelitian ini berjumlah 34 ibu hamil. Teknik sampling menggunakan sampling jenuh yaitu semua anggota populasi dijadikan sampel. Objek penelitian ini adalah emesis gravidarum dan aromaterapi lemon. Penelitian telah dilaksanakan di Puskesmas Wonogiri Kotabumi Lampung Utara pada bulan Juni - Juli 2021. Pengumpulan data menggunakan lembar kuesioner. Analisi data secara univariat dan bivariat (uji t).Hasil penelitian: rata-rata mual muntah sebelum diberikan aromaterapi lemon adalah 8,7, sedangkan rata-rata mual muntah sesudah diberikan aromaterapi lemon adalah 6,4.KesimpulanAda pengaruh pemberian aromaterapi lemon terhadap emesis gravidarum pada ibu hamil TM 1 di Puskesmas Wonogiri dengan p-value 0,000.Saran : Diharapkan untuk ibu hamil agar dapat menggunakan aromaterapi lemon dalam mengatasi mual muntah dalam kehamilan. Kata Kunci : Aromaterapi Lemon, Mual Muntah